POST-COMMUNIST DYNAMICS OF PUBLIC MEMORY: POLITICAL ANALYSIS - Волянюк, О.Я. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Noted that each political regime in their community affects its ability to store and transmit significant social meanings. Transitional political regimes characterized previously banned rehabilitation of historic themes, but also citizens are not prepared to adopt and critical thinking of the past. Memory of a democratic society is dynamic and open to dialogue.